Embryo-derived trypsin-induced calcium entry is inhibited by endometrial infertility factor, LEFTY2 - Yang, Zhiqi; Yan, Jing; Kull, Steffen; Alauddin, Md.; Brucker, Sara Y.; Henes, Melanie; Lang, Florian; Salker, Madhuri S. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionA transient window of uterine receptivity ensures that embryos implant in an optimal endometrial environment. Failure to establish or premature closure of the implantation window is thought to be a major cause of infertility, which affects many couples globally. Embryos release trypsin, which designates its developmental potential and plays a crucial role in implantation. Calcium (Ca2+) signalling participates in receptivity and is thus a prerequisite for embryo implantation. Left-right determination factor 2 (LEFTY2) is a negative regulator of endometrial receptivity and is associated with unexplained infertility. We hypothesize that LEFTY2 impedes Ca2+ entry induced by trypsin in endometrial cells.MethodsIn silico analysis was performed to investigate classical trypsin pathway genes in human embryos. Trypsin levels from single human embryo conditioned medium were subject to ELISA. To determine if trypsin signals can modulate calcium entry, intracellular calcium [Ca2+]i was determined utilizing Fura-2 fluorescence in human endometrial epithelial cells (Ishikawa cells). Bioinformatic analysis on publicly available single cell sequencing data was used to investigate the expression of L-type calcium channel (CACNA1C) in endometrium. qRT-PCR and immunofluorescence were used to quantify L-type calcium channel abundance.ResultsWe report that the trypsin machinery is established at the blastocyst stage and that high levels of trypsin are associated with a successful pregnancy. Treatment with LEFTY2 or combined treatment with LEFTY2 and trypsin blocked the increase of L-type Ca2+ channel levels and activity. Treatment of endometrial cells with trypsin was followed by an increase of [Ca2+]i, an effect that was significantly blunted by amiloride and LEFTY2. Further, the trypsin induced increase of [Ca2+]i was significantly blunted by L-type calcium channel inhibitor nifedipine. In the presence of nifedipine, LEFTY2 did not further modify trypsin induced increase of [Ca2+]i. LEFTY2 significantly decreased levels of L-type Ca2+ channel.DiscussionTaken together, we demonstrate that high trypsin levels are associated with a positive pregnancy outcome and that infertility factor LEFTY2 downregulates trypsin induced Ca2+ increase due in part by interference with nifedipine sensitive Ca2+ entry. These findings contribute further to our knowledge of unexplained infertility and failed assisted reproductive technologies.